Kemampuan Menulis Paragraf Deskriptif Siswa Kelas V SD Negeri 6 OKU Menggunakan Model Pembelajaran Inquiri Based Learning - Awalludin Awalludin; Rita Nilawijaya; Tri Riya Anggraini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2023)
The purpose of this study was to determine the learning of Indonesian with using learning model inquiri Based Learning in Class V SD Negeri 6 OKU, and to investigate the increase in students' ability in writing descriptive paragraphs using learning model inquiri Based Learning. The method used in this study is an action research methods class. Data collection techniques, namely tests and observation techniques, and techniques of analyzing data is done by analyzing test data and observations data. Based on the entire population and sample 25 students, through writing test descriptive paragraphs in the first cycle increased, ie 61.32 during the pre cycle and increased to 74, 64 in the first cycle, and 1, 76 in cycle II. Based on the results of the second cycle all students have reached the standard overall KKM. Based on the result of test can be concluded that the students of Class V SD Negeri 6 OKU were able to write descriptive paragraph by using learning model of Inquiry Based Learning. As for advice to Indonesian teachers in general, it is advisable to try to apply this learning inquiri Based Learning in learning Indonesian.